Autonomic responses to tooth clenching and handgrip test. (4th July 2022) - Tapiainen, Atte A.; Zaproudina, Nina; Lipponen, Jukka A.; Tarvainen, Mika P.; Vierola, Anu; Rissanen, Saara M.; Karjalainen, Pasi A.; Närhi, Matti
Abstract: Objective: The aim was to study the differences in autonomic nervous system activation between maximal tooth clenching task and handgrip test during and after the tasks. Also, the possible activation of trigeminocardiac reflex during the clenching task was explored. Material and methods: We compared autonomic responses to maximal tooth clenching and handgrip in 28 participants. Responses in heart rate variability, heart rate, and blood pressure were evaluated before, during, and after tests. Although all study participants were considered healthy during recruitment, 14 of them showed painful temporomandibular disorders in the clinical examination, which was taken into account in the analyses. Results: Handgrip and tooth clenching caused similar autonomic responses. However, tooth clenching seemed to activate the trigeminocardiac reflex shown as clenching-related vagal activation. The painful signs of temporomandibular disorders may interfere with the heart rate variability both at the baseline and during both tests causing significant variation in them. Conclusions: Both handgrip and tooth clenching affect the autonomic nervous system function. Tooth clenching differs from the handgrip due to trigeminocardiac reflex. Painful signs of temporomandibular disorders are interfering with the results of the tests and maybe underestimated in the studies of autonomic responses to both tasks.